2021
DOI: 10.1016/j.apsb.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LIM kinase reduces contraction and proliferation in bladder smooth muscle

Abstract: Overactive bladder (OAB) is the most bothersome symptom in lower urinary tract symptoms (LUTS). Current pharmacologic treatment aims to inhibit detrusor contraction; however, shows unsatisfied efficacy and high discontinuation rate. LIM kinases (LIMKs) promote smooth muscle contraction in the prostate; however, their function in the bladder smooth muscle remains unclear. Here, we studied effects of the LIMK inhibitors on bladder smooth muscle contraction and proliferation both in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…LIMK1 and TESK1 are, therefore, two key components of the signal transduction pathways that link extracellular stimulation to changes in cytoskeletal structure ( 49 , 50 ). It was reported that the N-terminal kinase of TESK1 may be a putative candidate accounting for LIMK-independent cofilin phosphorylation, as it shows approximately 50% amino-acid identity with LIMK ( 51 , 52 ). On the other hand, cofilin is activated by dephosphorylation by the phosphatase SSH1.…”
Section: Discussionmentioning
confidence: 99%
“…LIMK1 and TESK1 are, therefore, two key components of the signal transduction pathways that link extracellular stimulation to changes in cytoskeletal structure ( 49 , 50 ). It was reported that the N-terminal kinase of TESK1 may be a putative candidate accounting for LIMK-independent cofilin phosphorylation, as it shows approximately 50% amino-acid identity with LIMK ( 51 , 52 ). On the other hand, cofilin is activated by dephosphorylation by the phosphatase SSH1.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA synthesis assay was performed using the Cell-Light EdU Apollo 567 In Vitro Imaging Kit (RIBOBIO, Guangzhou, China) according to the manufacturer's instructions 22 . Briefly, cells were seeded in 96-well plates at a density of 1 × 10 5 per well, and 24 h later, 50 μmol/L EdU was added to the culture medium and incubated for 4–6 h. The cells were then fixed for 30 min in 4% paraformaldehyde, permeabilized for 10 min using 0.5% Triton-X 100, and stained for 30 min with 10 μmol/L Apollo 567.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the analysis process is time-consuming, presenting challenges for obtaining real-time results. Hence, surface plasmon resonance (SPR), [7][8][9] surface enhanced Raman scattering (SERS), [10][11][12] and electrochemical methods like electrochemical impedance spectroscopy (EIS) [13][14][15] or cyclic voltammetry (CV) [16][17][18] have been employed to expedite detection. These methods provide rapid responses and high sensitivity, enabling the detection of low concentrations of target substances.…”
Section: Introductionmentioning
confidence: 99%